Case Analyses on Implicit Academic Misconduct in Cross-Lingual Plagiarism - Zhang, Cheng (International Journal of Social Sciences and Public Administration, 2025)
Cross-lingual plagiarism-especially in the form of implicit academic misconduct-poses significant challenges to academic integrity, particularly in multilingual research contexts. This study explores the nuanced features of implicit academic misconduct within cross-lingual plagiarism, including syntactic interference, terminological inconsistency, inaccurate modifiers, and missing citations. Drawing on representative cases informed by real-world academic supervision, the paper illustrates how these subtle forms of misconduct often evade standard detection tools. The findings highlight the limitations of current plagiarism detection systems in capturing non-literal and multimodal content reuse. The study emphasizes the need for increased awareness, improved supervisory practices, and the development of more robust, cross-lingual-sensitive detection mechanisms to uphold academic integrity in increasingly globalized academic environments.